Transformational Leadership, Organizational Culture And HR Quality On University Mission Achievement: The Moderating Role Of Group Cohesion - Moh Romzi; Juri Wahananto; Shobihatul Fitroh Noviyanti; Ahmad Rifai; M. Adi Kulsum (International Journal of Interdisciplinary Research, 2026)
This research examines the effect of transformational leadership, organizational culture, and the quality of human resources on the effectiveness of achieving higher education institutions' missions, with group cohesion as a moderating variable. The study was conducted at IAIN Madura, employing a quantitative methodology, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were gathered through structured questionnaires distributed to academic and administrative staff. The results demonstrate that transformational leadership, organizational culture, and human resource quality significantly and positively influence institutional mission achievement. Furthermore, group cohesion enhances these relationships, highlighting its essential role in fostering a cohesive and goal-oriented organizational climate. These findings underscore the necessity of strategic leadership and a robust organizational culture in strengthening institutional performance. The study offers practical implications for academic leaders, emphasizing the importance of building group cohesion to amplify the effectiveness of leadership, organizational culture, and human resource quality. Future research is recommended to extend these findings by investigating the dynamics in different higher education settings and incorporating longitudinal approaches to explore the temporal impact of these variables.